(untitled) - Naganuma, Naoe (Tokyo, 1970)
The purpose of this book is to furnish the student studying naganuma's basic Japanese course with the necessary information with regard to the vocabularies, phrases, construction patterns as well as grammatical and other points which will prove useful to student. In fact of the points which the teacher will find it necessary to explain in English are all taken care of.
Keywords: Japanese language